The Citizens' Satisfaction on Service Quality of Mobile Government (Case Study : Wargaku Surabaya Application) - Yuliantini, Lisa Sophia; Purnomo, Eko Priyo (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2024)
This research aims to analyze the citizens’ satisfaction with the service quality of a mobile Government application named WargaKu Surabaya, by using the Mobile Government Service Quality (SQ-mGov) measurement involving four indicators, namely connectivity, interactivity, authenticity, and understandability. The research method used was quantitative using SmartPLS version 0.3 software with primary data sources in the form of questionnaires totaling 100 respondents. This research is interesting because it discusses citizens’ satisfaction with the quality of government services using parameters for measuring the quality of mobile government services. The research results show that the connectivity and understandability influence the citizens’ satisfaction with the service quality of WargaKu Surabaya application. However, the interactivity and authenticity do not affect the citizens’ satisfaction on WargaKu Surabaya application. The practical implications of this research can be used as an input for the government to improve the quality of mobile government services, particularly WargaKu Surabaya application, with the hope that as the service quality mobile Government increases, the citizens’ satisfaction will also improve.